Association Between Helicobacter pylori Infection and Nonalcoholic Fatty Liver Disease (NAFLD): A Cross-Sectional Study - Jibran Umar Ayub Khan, Humera Fayaz, Abdul Wahab, Zia Ul Haq, Syeda Iffat, Intikhab Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In patients with gastrointestinal symptoms Helicobacter pylori has been known to cause non alcoholic fatty liver disease However, there is still gap in literature regarding it in our local clinical setting population. Objective: The study aims to determine association between Helicobacter pylori Infection and Nonalcoholic Fatty Liver Disease Materials & Methods: The cross-sectional study was done on 100 patients at the MMC General Hospital, from January 2022 to June 2022. Participants with both abdominal ultrasound (US) for diagnosing fatty liver disease and stool antigen for the detection of H. pylori infection were included. The pros and corns as well as rationale of the study were clearly explained to the participants with an option to withdraw from the study if needed .The data analysis was done by SPSS version 25. Results: Among cases 15(30%) patients were male and 35(70%) were female while among controls 16(32%) were male and 34(68%) were female. Among cases 35(70%) patients and among controls only 18(36%) participants were positive for H-Pylori. Frequency of H-Pylori infection was significantly higher among cases as that of controls. i.e. 70% vs. 36%, p-value<0.001 Odds ratio of 4.14 shows that among cases risk of H-pylori infection was 4.14 times higher as compared to controls. Data entry and analysis was done with SPSS version-25. Quantitative variables were presented with mean±SD and qualitative variables with frequency and percentage.Frequency of H-Pylori was compared among cases and controls with Chi Square test. Conclusion: There is an association between NAFLD and Hpylori indicating the need for regularly screening such patients. Keywords: NAFLD, H Pylori